2020
DOI: 10.1038/s41385-019-0232-7
|View full text |Cite
|
Sign up to set email alerts
|

IL-4Rα expression by airway epithelium and smooth muscle accounts for nearly all airway hyperresponsiveness in murine allergic airway disease

Abstract: Airway hyperresponsiveness (AHR) often defines asthma. Murine allergic airway disease (AAD), like human eosinophilic asthma, is characterized by AHR, eosinophilia, goblet cell metaplasia (GCM), smooth muscle hypercontractility and increased production of IL-4 and IL-13—cytokines that induce these characteristics by binding to the IL-4Rα chain. We evaluated the epithelial and smooth muscle IL-4Rα-dependent contributions to AHR of BALB/c mice that possessed 0–2 functional IL-4Rα alleles and had airway disease in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…A second limitation of our study is that the underlying molecular mechanisms were not investigated. For example, previous studies have shown that IL-4 and IL-13 signaling are required for the manifestation of AHR in BALB/c mice exposed to HDM ( Johnson et al, 2007 ; McKnight et al, 2020 ). Further studies will be required to determine whether these types of signaling pathways are ultimately shaping the different susceptibility of C57BL/6 and BALB/c mice to develop AHR by differently modulating ASM contractility.…”
Section: Discussionmentioning
confidence: 99%
“…A second limitation of our study is that the underlying molecular mechanisms were not investigated. For example, previous studies have shown that IL-4 and IL-13 signaling are required for the manifestation of AHR in BALB/c mice exposed to HDM ( Johnson et al, 2007 ; McKnight et al, 2020 ). Further studies will be required to determine whether these types of signaling pathways are ultimately shaping the different susceptibility of C57BL/6 and BALB/c mice to develop AHR by differently modulating ASM contractility.…”
Section: Discussionmentioning
confidence: 99%
“…Although targeting Th2 cytokines are not particularly novel, there is continued interest in targeting this pathway in selected asthma endotypes. Recent studies suggest that epithelial cell responses to IL-4/IL-13 increases the IL-4Rα-dependent smooth muscle contribution to airway hyper-responsiveness, supporting IL-4Rα-targeted therapy in asthma (168). Activation of estrogen receptor-β signaling has been shown to downregulate airway hyper-responsiveness and airway remodeling (169).…”
Section: Mesenchymal Cells As "Effectors" Of Airway Remodelingmentioning
confidence: 99%
“…IL-13 acts on different cell types to induce airway remodeling, such as airway epithelial cell [5] and broblasts [6]. More importantly, IL-13 also acts on ASMCs via IL-4 receptor α (IL-4Rα) to participate in AHR [7].…”
Section: Introductionmentioning
confidence: 99%